(untitled) (International Journal of Physiotherapy, 2016)
Background: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. The major manifestation of COPD includes dyspnea, decreased oxygenation and reduced exercise tolerance. The other manifestations such as urinary incontinence are less noted and treated inadequately. The prevalence of urinary incontinence in Indian COPD population has not been well documented. The treatment of urinary incontinence includes pelvic floor exercises (Kegel’s exercises), biofeedback, and acupuncture etc. Methods: Forty female moderate COPD patients diagnosed according to American Thoracic Criteria with a complaint of urinary incontinence were selected for the study. Pelvic floor therapy exercises were given daily 5 sets per day (1 set =1-3 counts) for seven days. Baseline evaluation was done using International Consultation on Incontinence Short Form (ICIQ-SF) on the day of referral for physiotherapy and the post study measurements were taken on 7th day of hospital stay. Wilcoxon Signed Rank calculator was used to assess the data collected. Results: The z value of ICIQ-SF questionnaire was 5.5109 ( p≤ 0.05) based on Wilcoxon Sign rank test and it was significant when we compared the pre and post test mean difference. The pre test mean score of ICIQ-SF was 14.175 and post test mean score was 4.4.Based on the findings, the results showed significant improvement in patient symptoms and reduced stress incontinence post pelvic floor therapy exercises. Conclusion: The study emphasizes the importance of pelvic floor therapy in treating stress urinary incontinence among COPD patients and it should also be included in a comprehensive pulmonary rehabilitation program.